HIV self‐testing and oral pre‐exposure prophylaxis are empowering for sex workers and their intimate partners: a qualitative study in Uganda. Issue 9 (2nd September 2021) - Mujugira, Andrew; Nakyanzi, Agnes; Kasiita, Vicent; Kamusiime, Brenda; Nalukwago, Grace K.; Nalumansi, Alisaati; Twesigye, Chris C.; Muwonge, Timothy R.; Baeten, Jared M.; Wyatt, Monique A.; Haberer, Jessica E.; Ware, Norma C.
Abstract: Introduction: HIV self‐testing (HIVST) and oral pre‐exposure prophylaxis (PrEP) are complementary, evidence‐based, self‐controlled HIV prevention tools that may be particularly appealing to sex workers. Understanding how HIVST and PrEP are perceived and used by sex workers and their intimate partners could inform prevention delivery for this population. We conducted qualitative interviews to examine ways in which HIVST and PrEP use influence prevention choices among sex workers in Uganda. Methods: Within a randomized trial of HIVST and PrEP among 110 HIV‐negative cisgender women, cisgender men and transgender women sex workers (NCT03426670), we conducted 40 qualitative interviews with 30 sex workers and 10 intimate partners (June 2018 to January 2020). Sex worker interviews explored (a) experiences of using HIVST kits; (b) how HIVST was performed with sexual partners; (c) impact of HIVST on PrEP pill taking; and (d) sexual risk behaviours after HIVST. Partner interviews covered (i) introduction of HIVST; (ii) experiences of using HIVST; (iii) HIV status disclosure; and (iv) HIVST's effect on sexual behaviours. Data were analysed using an inductive content analytic approach centering on descriptive category development. Together, these categories detail the meaning of HIVST and PrEP for these qualitative participants. Results: Using HIVST and PrEP was empowering for this group of sex workers and their partners. Three types of empowerment were observed: (a) economic; (b) relational; and (c) sexual health. (i) Using HIVST and PrEP made sex without condoms safer. Sex workers could charge more for condomless sex, which was empowering economically. (ii) Self‐testing restored trust in partners' fidelity upon being reunited after a separation. This trust, in combination with condomless sex made possible by PrEP use, restored intimacy, empowering partnered relationships. (iii) HIVST and PrEP enabled sex workers to take control of their HIV prevention efforts and avoid the stigma of public clinic visits. In this way they were empowered to protect their sexual health. Conclusions: In this sample, sex workers' use of HIVST and PrEP benefitted not only prevention efforts, but also economic and relational empowerment. Understanding these larger benefits and communicating them to stakeholders could strengthen uptake and use of combination prevention interventions in this marginalized population.